Betsy Ross, designer of our flag - Weil, Ann (Indianapolis The Bobbs-Merrill Company, 1983)
Recreates the childhood of the woman traditionally remembered as the maker of the first American flag, which was secretly presented to General George Washington in Philadelphia in 1776.
Keywords: Ross, Betsy -- 1752-1836 -- Juvenile literature; Revolutionaries -- United States -- Biography -- Juvenile literature; Flags -- United States